Rational design of FVIII sialylated peptides to target Siglec-3 and Siglec-9 and improve peptide formulations for reverse vaccines - Nardini, Eleonora; Keumatio Doungstop, Brigitte-Carole; Gerpe-Amor, Tania; de Haas, Aram M.; de Kok, Mike; Peterse, Evert; Kalay, Hakan; Li, Rui-Jún E.; Chiodo, Fabrizio; Silipo, Alba; Voorberg, Jan; van Kooyk, Yvette (Frontiers in Bioengineering and Biotechnology, 2025)
Reverse vaccine formulations have shown their potential for the treatment of allergies and other autoimmune diseases by the design of antigens that modify dendritic cell function towards tolerogenic responses. We here demonstrate that modification of an immunodominant peptide from factor VIII (FVIII) with a tolerizing molecule, sialic acid, improves existing peptide formulations towards the induction of tolerogenic cytokine secretion by DCs. Sialic acids are the end-standing moiety of mammalian N- and O- glycans, which are naturally recognized as self-associated molecular pattern. In this paper we show that sialic acid modified FVIII peptides target Siglec-3 and -9 on DCs and increase IL-10 secretion. Our work proposes a method to select, synthetize and test sialylated immunodominant peptides with the aim of ameliorating the efficacy of peptide immunotherapy. Based on our results, we propose that the sialylated FVIII peptide designed in this study may be useful for re-establishing tolerance to FVIII in hemophilia A patients who developed neutralizing antibodies following treatment.